THE EFFECT OF MATOS SOIL STABILIZER AS AN ADDITION MIXTURE ON INDEX PROPERTIES OF SOIL STABILIZED WITH CEMENT - Maulana,Muhammad.Y F (Journal of Applied Science, Engineering and Technology, 2023)
All civil engineering constructions are built on or supported by soil, making the stability and safety of the structures dependent on the soil's bearing capacity. In road pavement structures, poor-quality pavement layers can lead to reduced support for the road pavement layers. Therefore, stabilization efforts are undertaken to address this issue. The objective of this research is to investigate the influence of matos soil stabilizer mixtures with varying matos content of 0%, 1%, 2%, 4%, and 8%, combined with a cement content of 5%, and different curing times of 0, 7, and 14 days on the classification and index properties of the soil. The results indicate that the index properties of the soil improve with different curing times of the cement and matos mixtures. This can be observed through a decrease in the soil's plasticity index, an increase in bulk density, a decrease in permeability coefficient, a decrease in water content and wet unit weight of the soil with longer curing periods. Additionally, the soil classification shows a more granular nature compared to the original soil.